Raised intraocular pressure as a potential risk factor for visual loss in Leber Hereditary Optic Neuropathy. - Anais Thouin; Philip G Griffiths; Gavin Hudson; Patrick F Chinnery; Patrick Yu-Wai-Man (PLoS ONE)
Leber Hereditary Optic Neuropathy (LHON) is an important cause of inherited mitochondrial blindness among young adults. The majority of patients carry one of three mitochondrial DNA (mtDNA) point mutations: m.3460G>A, m.11778G>A and m.14484T>C, all of which affect critical complex I subunits of the mitochondrial respiratory chain. LHON is characterised by marked incomplete penetrance, clearly implying that the mtDNA mutation is insufficient on its own to trigger retinal ganglion cell dysfunction and visual loss. In this case series of three affected patients harbouring the m.11778G>A mutation, we provide evidence suggesting that raised intraocular pressure could be a risk factor triggering visual loss in at-risk LHON carriers.